High-resolution isochronous stratigraphic framework through well-seismic integration in tight sandstone: a case study of Luodai gas field, Sichuan, China - Luo, Chuanjiang; Wang, Changcheng; Lu, Gang; Zhang, Sheng; Lan, Zhiguio; Li, Tang; Dong, Ruibin; Sun, Jiaqian; Huang, Lisheng (Frontiers in Earth Science, 2024)
Tight gas sandstone represents a significant unconventional resource extensively discovered across numerous sedimentary basins around the world. Tight sandstone reservoirs are characterized by low porosity, low permeability, variable source material, rapid spatial and temporal changes, poor reservoir properties, and strong heterogeneity. Traditional geophysical methods struggle to meet the demands of exploration and development of these types of reservoirs. This study applies a high-precision comparative approach using well-seismic integration to establish a relative isochronous stratigraphic framework. Based on this framework, extracting seismic properties can effectively predict tight sandstone reservoirs. This paper, focusing on the Penglaizhen Formation in the Luodai Gas Field of the Western Sichuan Jurassic system. This entire process accomplished in three steps: starting with regional marker layers as the initial framework; followed by the establishment of a relative isochronous framework through precise well-seismic integration; and finally stratigraphic slicing techniques to delineate isochronous stratigraphic framework with shorter time intervals. Thereby enhancing the reliability of subsurface stratigraphic information and data accuracy. The study posits that current technological means cannot create a truly isochronous stratigraphic framework; thus, “isochronous” is considered a relative concept in this context. The framework aims to ensure temporal consistency by minimizing discrepancies through mutual constraints between well and seismic data, serving to exploration and development requirements. Furthermore, analyses such as sensitive attribute extraction, impedance inversion, and assessment of hydrocarbon potential in tight sandstone reservoirs demonstrate strong correlation with drilling results. This validation underscores the framework’s efficacy in interpreting industrial gas production flows, thereby providing robust support for future oil and gas exploration.